Transformational Leadership, Learning Orientation,Creative Selfefficacy And Employee Creativity A Study Of Smes In China - Qian, Chiqing (2024)
Employee creativity is critical for the sustained growth and competitiveness of small and medium-sized enterprises (SMEs). Despite its importance, limited research has focused on understanding the factors that drive employee creativity in resourceconstrained settings such as Chinese SMEs. Addressing this gap, this study explores the relationships among transformational leadership, learning orientation, creative self-efficacy, and employee creativity within the context of Chinese SMEs. Specifically, this research examines the mediating role of creative self-efficacy on the relationship between transformational leadership, learning orientation, and employee creativity. Grounded in Social Cognitive Theory, the study proposes a research framework that positions transformational leadership and learning orientation as key predictors of employee creativity, with creative self-efficacy serving as a mediating variable. An online questionnaire was distributed to employees across various Chinese small and medium-sized manufacturing enterprises, resulting in responses from 742 participants. Data were analyzed using hierarchical linear modeling, revealing that transformational leadership and learning orientation have a significant positive relationship with employee creativity. Additionally, creative self-efficacy was found to be a significant mediator in the relationship between transformational leadership, learning orientation, and employee creativity. The findings provide valuable insights for both employees and managerial stakeholders in Chinese SMEs, highlighting actionable strategies to enhance employee creativity.